Stakeholder-Associated Life Cycle Risks in Construction Supply Chain - Koc, Kerim; Gurgun, Asli Pelin (ASCE-AMER SOC CIVIL ENGINEERS, 2021)
Numerous inherent risks impose a systematic risk identification approach to achieve supply chain performance goals in construction projects. This paper investigates supply chain risks in construction projects with respect to life cycle and corresponding stakeholders. The research was organized with two stages. In the first stage, a systematic literature review accompanied by a content analysis was conducted based on risks in construction supply chains (CSCs) to identify research gaps, suggest future research directions, and support subsequent steps. Then, three focus group discussions (FGDs) were performed by industry representatives to (1) specify life cycle risks in CSCs, (2) associate specified risks to related stakeholders, and (3) ensure the role of each stakeholder in CSCs. Results of the content analysis indicate that relationship, communication, and sustainability are the most frequently examined research areas, while innovation and organizational learning, supplier vulnerability, and negotiation are overlooked in the literature. Based on sessions of FGDs, 135 risks were categorized into 10 phases of construction supply chain life cycle (SCLC) as requirement and demand, design, tendering and contracting, manufacturing, logistics, hand over, inventory, installation, winding up, and control and maintenance. Main contractor, subcontractor, supplier, and client were found as the critical decision entities in tendering and contracting, installation, logistics, and requirement and demand phases, respectively. The findings can be useful for researchers by indicating research gaps, and for construction companies seeking to increase their supply chain performance through life cycle and stakeholder approaches.
Keywords: Construction supply chain; Supply chain risks; Content analysis; Supply chain life cycle; Supply chain stakeholders; Focus group discussion; MANAGING RISKS; MANAGEMENT; INDUSTRY; FUZZY; Engineering